تأثير استخدام طريقة التدريبات في إتقان علم الصرف لطلاب مدرسة المختار المتوسطة الإسلامية بكاسي الشمالية - Farandika, Azzahra Rabi; Matin, Iman; Fudhaili, Achmad (Program Studi Bahasa dan Sastra Arab Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
This study aims to examine the effect of using the drill method on students’ mastery of Ilmu Sharaf (Arabic morphology) at Ma'had Al-Mukhtar Islamiy, North Bekasi. The researcher employed a quantitative approach with a quasi-experimental research design. The sample consisted of two groups: an experimental group that received instruction using the drill method and a control group that received conventional teaching. Data were collected through pre-tests and post-tests and analyzed using statistical tests to determine the effectiveness of the drill method in enhancing the mastery of Ilmu Sharaf. The results indicated a significant improvement in the experimental group's mastery compared to the control group. The average pre-test score of the experimental group was 62.3, which increased to 82.7 in the post-test. In contrast, the control group's average pre-test score was 60.1, rising to 70.4 in the post-test. Statistical analysis showed that the drill method had a more significant impact on improving Ilmu Sharaf mastery compared to conventional methods. Moreover, the drill method also enhanced students' motivation to learn Ilmu Sharaf more actively and systematically. The findings suggest that the drill method is effective in improving students' understanding and mastery of Ilmu Sharaf. This study can serve as a recommendation for educators to adopt similar methods in Arabic language instruction to achieve more optimal learning outcomes.